1994
DOI: 10.1002/ajim.4700250610
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among danish merchant seamen from 1970 to 1985

Abstract: A retrospective cohort study was performed to analyze the mortality patterns of Danish merchant seamen in the period 1970-1985. The population census in 1970 in Denmark was the source of information on individual occupation, age, and marital status. All men aged 20-64 years and economically active in 1970 were included. Computerized linkage with the Danish Mortality Register gave information about the deceased persons' date and cause of death. An increased overall mortality among all groups of seamen was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 10 publications
3
46
0
Order By: Relevance
“…This is a fierce change compared to previous conditions. Several previous Danish studies have shown the heavy health impact of smoking and alcohol consumption among Danish seafarers [13,[29][30][31].…”
Section: Consumption Of Tobacco and Alcoholmentioning
confidence: 99%
“…This is a fierce change compared to previous conditions. Several previous Danish studies have shown the heavy health impact of smoking and alcohol consumption among Danish seafarers [13,[29][30][31].…”
Section: Consumption Of Tobacco and Alcoholmentioning
confidence: 99%
“…In a number of studies from different countries, seamen have been found to show increased rates of mental illness and mortality [Brandt et al, 1994;Kelman and Kavaler, 1990;Leigh and Jiang, 1993;Otterland, 1960;Rapiti et al, 1992;Sundby and Nyhus, 1963;Sundby, 1956;Vuksanovic and Goethe, 1986;Ågren and Romelsjö, 1992;Ö degård, 1945;Ö degård, 1956]. Alcohol consumption also seems to be high among seafarers [Brun-Gulbrandsen and IrgensJensen, 1967;Olkinuora, 1984;Powdermaker, 1945;Rose and Glatt, 1961;Whitehead and Simpkins, 1983;Åmark, 1951].…”
Section: Introductionmentioning
confidence: 95%
“…The results indicated an increased risk of all cancers, larynx cancer, stomach cancer, and lung cancer (1). Scandinavian studies dealing with cancer risk among deck officers in particular have shown an increased risk of all cancers (2,3), lung cancer and larynx cancer (3), nonmelanoma skin cancer (3,4), kidney and brain cancer (4), and soft-tissue sarcoma (3).…”
mentioning
confidence: 96%